Analisis Determinan Kebijakan Dividen dengan Ukuran Perusahaan sebagai Variabel Moderasi (Studi Empiris pada Perusahaan Pertambangan Indonesia Tahun 2016-2020) - Eli Maslika ‘Atin; Harjum Muharam (Diponegoro Journal of Management, 2022)
Dividend policy in the company is a crucial matter because it can affect the valueof the company in the future. To support this, increasing the value of the company is one ofthe main goals of the company. A higher dividend payout will relatively increase the share price, which means an increase in the value of the company. The complexity of thecompany's activities has increased the conflict of interest between stakeholders and company management. The company makes a clear distinction between ownership, operations and management. This division allows management to prioritize the interests of the company or its owners. These phenomena and gaps are the basis for conducting this research. This research has the aim of explaining and knowing the determination of dividend policy in mining companies in Indonesia, either in the form of significance or in the formof influence. Data retrieval from this study involved 46 companies with a total of 230 data which were analyzed using the classical assumption test and processed with the SPSS version 21 program. Based on this research, it was found that profitability has a positive and significant effect on dividend policy. In addition, liquidity has a negative and significant effect on dividend policy. In this study, it was also found that the company's growth had a negative and significant effect on dividend policy. Then lastly, company size which is a moderating variable has a positive and significant effect on the dependent variable of dividend policy